EFEKTIFITAS AIR REBUSAN LIDAH BUAYA TERHADAP PENURUNAN GLUKOSA DARAH PENDERITA DIABETES MELLITUS - Nurul Hidayah; Zurhayati Zurhayati (LLDIKTI Wilayah X, 2021)
Diabetes mellitus (DM) is a chronic disease which is still a major problem in the world of health in Indonesia, which occurs due to abnormalities in insulin secretion, insulin action or both. A report from the World Health Organization (WHO) states that diabetes mellitus is ranked 6th as the cause of death. About 1.3 million people die from diabetes and 4% die before the age of 70. The purpose of this study was to determine the effectiveness of Aloe Vera Decoction on the Blood Glucose Levels of the Elderly in Type II DM Patients in the Work Area of the UPT Puskesmas Harapan Raya Pekanbaru in 2020. This type of research is quantitative with a Quasi Experimental design that is one group posttest. The population in this study were 83 people with diabetes mellitus in the Harapan Raya Pekanbaru Health Center. sample by simple random sampling until the number of samples to be given intervention is 30 people. Data analysis using nonparametic test with Wilcoxon test obtained a value of Pvalue 0.000 <0.05, meaning that the hypothesis (Ha) is accepted, it is concluded that there are differences in blood glucose levels before and after being given Aloe Vera.